2021
DOI: 10.3389/fpsyg.2021.633530
|View full text |Cite
|
Sign up to set email alerts
|

More Hype Than Substance? A Meta-Analysis on Job and Task Rotation

Abstract: Although there exist numerous publications on job and task rotation from various disciplines, there is no consistent evidence of their effectiveness. Drawing on theories from industrial and organizational psychology, knowledge management, ergonomics, and management science, we meta-analytically investigated relationships between job/task rotation and employee attitudes, learning and development, psychological and physical health, and organizational performance. Due to a conceptual overlap and frequent confusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 124 publications
(142 reference statements)
1
13
0
Order By: Relevance
“…On a more general level, the overall rather low ratings in MWC for both, the traditional and digitized workplace in our vignette emphasize the need for work design interventions in assembly, such as task or job rotation (Mlekus & Maier, 2021 ). Task rotation “refers to the alternation between tasks within a job that can require different skills and responsibilities but is not associated with a change to a different function or department” (Mlekus & Maier, 2021 , p. 2), in this case, the alternation between assembly products. This task rotation is already an essential consequence of the individualized customer requests that characterize the digital factory of the future.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On a more general level, the overall rather low ratings in MWC for both, the traditional and digitized workplace in our vignette emphasize the need for work design interventions in assembly, such as task or job rotation (Mlekus & Maier, 2021 ). Task rotation “refers to the alternation between tasks within a job that can require different skills and responsibilities but is not associated with a change to a different function or department” (Mlekus & Maier, 2021 , p. 2), in this case, the alternation between assembly products. This task rotation is already an essential consequence of the individualized customer requests that characterize the digital factory of the future.…”
Section: Discussionmentioning
confidence: 87%
“…This task rotation is already an essential consequence of the individualized customer requests that characterize the digital factory of the future. Job rotation is defined as “a lateral transfer of employees within an organization without a change in salary or hierarchy” (Mlekus, 2021 , p. 2) and can include rotations not only in departments but whole units (Mlekus & Maier, 2021 ). Applying job rotation on a larger scale will be more challenging than using task rotation in this assembly context.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated job and task rotation (job rotation describes the rotation between whole jobs instead of tasks) and how they are related to positive employee or organizational outcomes (for a recent meta-analysis, see Mlekus and Maier, 2021 ). These relationships can be theoretically explained by Parker et al’s (2017a) framework of work design influences and the JCM ( Hackman and Oldham, 1976 ).…”
Section: Task Rotation As a Technology Featurementioning
confidence: 99%
“…It makes jobs richer in variety, and previous studies found that it was positively associated with a range of positive outcomes, such as job satisfaction, work motivation, performance, and psychological health (cf. for a recent meta-analysis, Mlekus and Maier, 2021 ). Such effects have, however, not yet been studied in the context of digital assistance systems.…”
Section: Introductionmentioning
confidence: 99%
“…Uncalled for cases of employee abuse, abrupt job rotation and employee transfers, and termination have been common since 2016. Whereas job rotation and employee transfers are regarded as best practices in management sciences (Mlekus & Maier, 2021) at KIU the intention of the transgressors is to frustrate the employees. Supervisors suffer from intermittent explosive disorder (IED) associated with sudden episodes of unwarranted anger.…”
Section: The Effect Of Displaced Aggression On Productivitymentioning
confidence: 99%